Pengaruh Aktivitas Menelusuri dan Mengunggah Konten Budaya di Instagram terhadap Pelestarian Nilai Budaya Bugis di Desa Arasoe - Rahma Fuji Rahayu; Nurlela Nurlela; Dimas Ario Sumilih (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
This study aims to examine the activity of browsing and uploading cultural content on Instagram towards the preservation of Bugis cultural values. This study uses a quantitative method with a causal associative design. The research sample consisted of 92 respondents who were active Instagram users in Arasoe Village, Bone Regency, selected through a purposive sampling technique. Data collection was conducted using a Likert scale, while data analysis used descriptive statistics and multiple linear regression with the help of SPSS. The results of this study indicate that the activity of browsing cultural content on Instagram has a partial effect. However, simultaneously, Instagram use still contributes to the preservation of local cultural values. This finding indicates that consumption of cultural content is more effective in strengthening awareness and internalization of Bugis cultural values than content production. Scientifically, this study contributes by distinguishing the role of consumption activities and content production in the preservation of digital culture and strengthens the application of Pierre Bourdieu's theory in the context of social media. Practically, the results of this study recommend the use of Instagram as a medium for cultural education by improving the quality of cultural content that is easily accessible to the younger generation.